The Effect of Teaching Based on TRIZ and Aptitude Strategies on Imaginative Thinking and Metacognition among Students of Arabic in Kuwait - Noura Alenzi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the effect of teaching based on the strategies of TRIZ and Aptitude on the development of imaginative thinking and metacognition in Arabic language among a sample of students in the seventh grade of primary school in the State of Kuwait. The sample of the study consisted of (30) female students; they were divided into two groups: an experimental group who studied according to the TRIZ and Aptitude strategies, and a control group who studied according to the usual method. The study followed a quasi-experimental method. Several lessons have been developed within the second unit (Journeys and Adventures) in Arabic language for the seventh grade, according to the strategies of TRIZ and Aptitude, and the test of imaginative thinking, and the Metacognition Skills Scale was used. The results of the study showed that there were statistically significant differences between the average scores of the two groups on the imaginative thinking test and the metacognitive skills scale in favor of the experimental group. Based on this result, the study recommends training teachers in Kuwait before and during service on unusual teaching strategies, especially those that depend on the strategies of TRIZ and Aptitude.